Factors Affecting the Value of Real Estate and Land - Baxrinova Moxigul Xo’jamurotovna (Research Parks Publishing LLC, 2022)
The article describes the factors influencing the value of real estate and land plots, factors of government regulation, the location of real estate and the factors influencing the accounting of real estate.